Postmastectomy Radiation Therapy: Are We Ready to Individualize Radiation? - Ashlyn S. Everett; Drexell Hunter Boggs; Jennifer F. De Los Santos (International Journal of Breast Cancer)
Contemporary recommendations for postmastectomy radiation have undergone a shift in thinking away from simple stage based recommendations (one size fits all) to a system that considers both tumor biology and host factors. While surgical staging has traditionally dictated indications for postmastectomy radiation therapy (PMRT), our current understanding of tumor biology, host, immunoprofiles, and tumor microenvironment may direct a more personalized approach to radiation. Understanding the interaction of these variables may permit individualization of adjuvant therapy aimed at appropriate escalation and deescalation, including recommendations for PMRT. This article summarizes the current data regarding tumor and host molecular biomarkers in vitro and in vivo that support the individualization of PMRT and discusses open questions that may alter the future of breast cancer treatment.